A new species of the genus Pseudohomonyx Arrow, 1908 (Coleoptera: Scarabaeidae: Dynastinae) from Malaysia and Thailand, with first description of P. apoensis Miyake & Yamaya, 1997 male and a catalogue of the genus - Geshev), Qiao-Zhi Yang (Georgi; Pathomwattananurak, Wuttipon (Zootaxa, 2023)
Pseudohomonyx continentalis Yang & Pathomwattananurak, new species from Malaysia and Thailand, is described and illustrated herein. Male of P. apoensis Miyake & Yamaya, 1997 is described and illustrated for the first time. Pseudohomonyx javanus (Burmeister, 1847) is newly recorded from Malaysia and Thailand. An annotated catalogue and a distribution map for the genus are also provided.